2005
DOI: 10.3147/jsfp.40.125
|View full text |Cite
|
Sign up to set email alerts
|

Aquabirnavirus-induced Protection of Marine Fish against Piscine Nodavirus Infection

Abstract: ABSTRACT--Experimental dual-infections with a non-lethal aquabirnavirus (ABV) and a lethal betanodavirus (redspotted grouper nervous necrosis virus: RGNNV) were carried out in Japanese flounder Paralichthys olivaceus and sevenband grouper Epinephelus septemfasciatus.In the dual-infection group, ABV was intramuscularly (IM) injected into fish seven days before the IM-injec tion with RGNNV. In the experiments with flounder, a high expression of an Mx gene, a molecular marker for type I interferon(s) (IFN) produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…These results were consistent with those observed in rainbow trout with Poly(I:C) injection and IHNV challenge (Kim et al 2008). Also, Japanese flounder and sevenband grouper pre-infected with ABV were protected from VHSV and/or RGNNV infection, and in that study it was confirmed that fish Mx gene, an indicator of IFN, was expressed after the ABV injection (Pakingking et al 2004(Pakingking et al , 2005. Kim et al (2009) demonstrated that an antiviral state was established by injecting rainbow trout with Poly(I:C), as a substitute for IPNV.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…These results were consistent with those observed in rainbow trout with Poly(I:C) injection and IHNV challenge (Kim et al 2008). Also, Japanese flounder and sevenband grouper pre-infected with ABV were protected from VHSV and/or RGNNV infection, and in that study it was confirmed that fish Mx gene, an indicator of IFN, was expressed after the ABV injection (Pakingking et al 2004(Pakingking et al , 2005. Kim et al (2009) demonstrated that an antiviral state was established by injecting rainbow trout with Poly(I:C), as a substitute for IPNV.…”
Section: Resultsmentioning
confidence: 73%
“…Furthermore, primary infection with ABV in Japanese flounder and sevenband grouper Epinephelus septemfasciatus involved protection of fish from other pathogenic viruses, such as VHSV and fish nodavirus (Pakingking et al 2003(Pakingking et al , 2005. It was also reported that protection from VHSV and infectious hematopoietic necrosis virus (IHNV) was induced in rainbow trout Oncorhynchus mykiss by pre-exposure to infectious pancreatic necrosis virus (IPNV), aquareovirus or a picornavirus (de Kinkelin et al 1992, Hedrick et al 1994, La Patra et al 1995, Byrne et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…An anti-VHSV activity was also demonstrated in the serum of Japanese flounder infected by an aquatic Birnavirus (ABV) and a high expression of a Mx gene, a molecular marker of type I interferon occurred in the head kidneys of the ABV-challenged flounder suggesting IFN activity [20]. It was also shown that ABV induced IFN activity against a secondary Betanodavirus infection [17].…”
Section: Introductionmentioning
confidence: 96%
“…The primary infection of Salmonids by an Aquabirnavirus, a Picornavirus or an Aquareovirus involves a protection of fish to other viruses such as viral haemorrhagic septicaemia virus (VHSV), IHNV [14e16] or Nodavirus [17]. This protection, transient or partial, has been shown both in vivo and in vitro [11,13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in marine fishes, primary infection of Japanese flounder and sevenband grouper Epinephelus septemfasciatus by aquabirnavirus confers protection from other pathogenic viruses, such as VHSV and fish nodavirus (Pakingking et al 2003(Pakingking et al , 2005. The protection from the secondary infection of virus was due to an interferon (IFN) activity induced in the fish by the primary infection (Pakingking et al 2004, Das et al 2007, McBeath et al 2007).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%